Ética e educação tecnológica: as práticas docentes de ética e cidadania organizacional nas escolas técnicas estaduais de São Paulo - Frias, Fernando Vinicius Gonçalves (2020)
The performance of the teachers of the Paula Souza State Center for Technological Education (CEET Paula Souza), regarding the teaching of the discipline Ethics and Organizational Citizenship was the object of study of this dissertation. How should ethics be viewed as a science that studies morals, should it shape actions, or construct reflections? Teachers, when teaching the content belonging to the subject, emphasize more the philosophical ethics or aesthetics desired by the professional profile of the area? Can the task of professionals from various academic backgrounds to teach such a discipline interfere with the content to be taught? What are the practices used by teachers to teach the curriculum component Ethics and Organizational Citizenship? It is hypothesized that some teachers, without the necessary foundation, end up making a commitment to teach classes, but do not have a commitment to teaching ethics, which even creates a high turnover of teachers who teach the component. Thus, do not promote dynamic and interesting practices, do not develop research and studies to improve the teaching of ethics, do not value the curriculum component, passing this disinterest to students, the teacher does not know and does not follow the course plan and often teach other content. at the moment they should be teaching ethics. To define “ethics” we searched the writings of Gilberto Cotrim e Mirna Fernandes, Marilena Chaui, Maria Lucia Arruda Aranha e Maria Helena Pires Martins, reference authors in public high schools in São Paulo, respectively with the works: Philosophy (2016), Initiation to Philosophy (2014) and Philosophying: Introduction to Philosophy (2013). The study also analyzes two works produced by the Paula Souza Center on the curricular component. The Freirean category “universal ethics of the human being”, present in Pedagogy of freedom (1996), led to the understanding of “teaching practice” used in this work. The methodological scope had four stages: exploratory research, bibliographic research, documentary research and field research with interviews and questionnaires, aiming to clarify if the practices promoted by the teachers have the philosophical or modeling nature in relation to the discipline “Ethics and Organizational Citizenship”.